Factors Affecting Motor Vehicle Taxpayer Compliance - PUTRA, Anak Agung Gede Wisnu Adi Pradana; KAWISANA, Putu Gede Wisnu Permana; INDRIYANI, Ni Made Vita (Journal of Entrepreneurial and Business Diversity, 2023)
Purpose: Tax is the most significant source of revenue for a country, especially Indonesia. Achieving the level of taxpayer compliance and maintaining the level of compliance is a matter of concern in both developed and developing countries. This study aims to determine the effect of service quality, religiosity, and subjective norms on individual taxpayer compliance at the Joint Samsat Office, Tabanan City.Methodology:The data analysis method used is multiple linear regression. This type of research is research with primary data obtained from the answers of individual taxpayers registered at the Joint Samsat Office in Tabanan City, namely answers to a series of questions from a questionnaire posed by researchers regarding the factors that influence taxpayer compliance. The sample was determined using nonprobability sampling with an accidental sampling technique.Findings: The results of this study indicate that good service quality, intense religiosity, and high subjective norms significantly affect individual taxpayer compliance registered with the Joint Samsat Office, Tabanan City.Implication:This research can motivate the Tabanan City Samsat Joint Office to maintain good service quality for the satisfaction and comfort of taxpayers in carrying out their tax obligations.